Augmented Reality Technology to Promote Analytical Thinking Abilities - Thasuwan, Wasinee (Academic MCU Buriram Journal, 2024)
The purpose of this article is to present the idea of augmented reality technology as a tool to promote analytical thinking ability in students. From the analysis results, it was found that at present, Thai society has developed and changed accordingly, especially the introduction of technology into the education of people in society that role in facilitating various aspects inevitably in particular, technology will help in understanding news in various areas according to the strategic plan. That involves creating media, media libraries, and digital learning resources or facilitating education to be faster, more accurate, and more accurate to support the changes in the world in the information technology era using augmented reality technology, also known as AR (Augmented Reality), is used in teaching and integrating learning management to develop analytical thinking abilities. Currently, augmented reality technology is being applied in a variety of educational fields in line with the development of essential skills in the 21st century and to promote self-learning the aim is for students to develop analytical thinking abilities. According to the principle of reason, it leads to the creation of wisdom. Today is the information age where learners have access to modern technology. As a result, student learning is flexible, not limited to just one type of learning. therefore, augmented reality technology is a tool to promote analytical thinking ability in students.In this article will about Concept and origin of augmented reality technology implication of augmented reality technology Evolution of augmented reality technology Working principle of augmented reality technology elements of augmented reality technology application of augmented reality technology learning management with augmented reality technology using augmented reality technology, for the purpose of develop analytical thinking abilities.